Labor revitalization global perspectives and new initiatives - Cornfield, Daniel B.; McCammon, Holly J., 1959- (Amsterdam ; London : JAI, 2003)
This work examines variations among nations in the wide array of initiatives labour unions and labour movements are taking to strengthen themselves and recruit new members. Moving beyond previous research on the factors leading to union decline, the international group of scholars who have contributed to this volume present a research agenda on the many initiatives unions are taking - and the different social, economic, and political challenges they face in several world regions, as labour movements endeavor to revitalize themselves. These revitalizing initiatives include changing labor leadership and membership organizing strategies; "social movement unionism"; broadening the range of services provided to union members; and pursuing political and legal reform that achieves freedom of association. The contemporary cases of labour revitalization in this volume have occurred in Australia, Brazil, Germany, Korea, Mexico, the Netherlands, the United Kingdom, the United States, and Venezuela. The research agenda presented here rests on the conceptualization of labour revitalization as "socially embedded action," or strategic action taken by labor unions to strengthen themselves by redefining their relationships with workers, employers and states. Each of the three parts of "Labor Revitalization" addresses labour's changing relationships with workers, employers, and states, respectively.
Reviving the labor movement: a comparative perspective / Lowell Turner -- Made in the USA, imported into Britain: the organizing model and the limits of transferability / Bob Carter ... et al. -- Organising for renewal: a case study of the U.K.'s organising academy / Edmund Heery ... et al. -- Revitalization of the labor movement in the Netherlands: with or without the traditional unions? / Leni Beukema and Harry Coenen -- Regional development and new labor strategies: trade unions and the new car plants in Resende, Brazil / Alice Rangel De Paiva Abreu and José Ricardo Ramalho -- Korean white-collar union's journey to labor solicarity: the historic path from enterprise to industrial unionism / Doowon Suh -- Labor revitalization? the case of Australia / Rae Cooper, Marc Wescott and Russell D. Lansbury -- Mexican trade unionism in the face of political transition / Enrique De La Garza Toledo -- Political transitionand labor revitalization in Mexico -- Graciela Bensusán and Maria Lorena Cook -- Relegitimazatiion of the union movement in Venezuela / Héctor Lucena.
Includes bibliographical references.
Description based on print version record.
Keywords: Labor unions -- Sociological aspects; Industrial relations -- Social aspects; Labor policy; Labor unions -- Political activity; Work -- Social aspects; Industrial sociology; Labour economics; Sociology: work & labour; Social Science -- Sociology -- General